Post-colonial careering and the discipline of geography: British geographers in Nigeria and the UK, 1945–1990. (October 2019) - Craggs, Ruth; Neate, Hannah
Abstract: Few geographers wrote explicitly about decolonisation. Yet the ends of empires wrought substantial changes to the discipline of geography. It impacted the places studied, the approaches deemed appropriate, the sites of geographical knowledge production, the lecturing jobs available, and the shape and extent of transnational networks. Focusing on the 'post-colonial careering' of British geographers who worked at the university at Ibadan, Nigeria before returning to academic posts in UK geography departments, this paper explores the interconnections between academic careers, geographical knowledge and decolonisation. It argues that we can understand these connections in three ways. First, geographers' careers were shaped in important ways by decolonisation; second, these experiences in turn shaped the discipline of geography in the (post)colonial world and the UK; and third, geographers' work at colonial universities and in Britain was not only influenced by, but was itself part of the process of decolonisation. The article contributes to understandings of decolonisation as registered, and actively produced, through academic research and careers, institutional development, and transnational networks. Uncovering the (post)colonial connections which shaped British geography in the post-war period broadens understandings of disciplinary history beyond those which focus on Anglo-American networks and offers opportunities to consider the lessons of these past disciplinary patterns and practices for contemporary geography. Highlights: Examines the careers of British geographers who worked in both Nigeria and the UK. Demonstrates that while few geographers studied decolonisation it changed the discipline substantially. Uses the concept of post-colonial careering to explore these professional lives. Explores how decolonisation was registered and actively produced through academic careers and transnational networks. Offers lessons from these past disciplinary patterns for geography today.